Pengembangan Bahan Ajar Berbasis Mind Mapping Mata Pelajaran IPA di MIS Serre Kabupaten Bulukumba - Shaleha, Ummy Mutiah; Usman; Muzakkir (Prodi PGMI IAI Sahid, 2024)
This study aims to develop Module Teaching Materials on the Material of the Respiratory System of Living Things for Grade V MI. The type of research used is research and development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The test subjects in the study were fifth grade students of MIS Serre Bulukumba. Based on the results of the limited trial conducted, it was found that the validation results were categorized as valid. (2) the level of practicality of the module is in the very good category. (3) the level of effectiveness of the module seen from the teacher's ability to manage learning with an average of 4.7 is on very good criteria. Student activity with an average of 86.7% where the results of the analysis of student activity are in the very active category and the student learning outcomes test gets an average score of 87. Based on the results of the study, it can be concluded that the Mind Mapping-based science learning module on the material of the respiratory system of living things is suitable for use in the learning process.